Recent Findings Pertaining To Factors Contributing To The Poor Academic Performance Of Undergraduate Students In The Department Of Electrical Engineering, University Of Malaya, Kuala Lumpur, Malaysia - Adikan, Faisal Rafiq Mahamd; Ali, N.M.; Mokhtar, Norrima; Mubin, Marizan (2009)

(untitled)
This paper discusses the factors contributing to the poor academic performance of undergraduate students at the Department of Electrical Engineering, in the Faculty of Engineering, University of Malaya. Amongst the factors found are social issues, poor self discipline, language problems, financial constraint and adjustment issues into university life. The Department has taken steps in its effort to overcome these problems. Part of these initiatives was the formation of a committee to oversee the situation of the poor performing students, and efforts have been stepped up to monitor and guide these students.